Metode Komunikasi Mudabbiroh dalam Meningkatkan Kedisiplinan Santriwati di Asrama Putri Pondok Pesantren Al-Ishlahuddiny Kediri Lombok Barat - Heriyadi; Isnaini Fitri (P3M STID Mustafa Ibrahim Al-Ishlahuddiny Kediri Lombok Barat, 2024)
Discipline is an influence designed to help children be able to face the environment. Discipline grows from the need to maintain a balance between an individual's tendencies and desires to act in order to obtain something, with the restrictions or regulations required by the environment for him. Discipline is necessary, because discipline is capital for achieving success. By having a disciplined attitude, a person will get used to things that make him habitually develop, do things on time and be able to develop his potential. The research focus in this thesis discusses how the mudabbiroh communication method improves female students' discipline in the girls' dormitory at Al-Ishlahuddiny Islamic boarding school, Kediri, West Lombok. Data was collected through observation, interviews and documentation with the provisions of triangulation, using reference materials and extending observations. The results of the research show that the application of the mudabbiroh communication method implemented by mudabbiroh is effective in improving the discipline of female students in the girls' dormitory. This can be seen from the increase in compliance with the rules in the girls' dormitory, the decrease in the number of violations, and the increased motivation of female students in obeying the rules and participating in activities in the girls' dormitory.